Exploring ACC deaminase-producing bacteria for drought stress mitigation in Brachiaria - Ferreira, Jéssica P.; Vidal, Márcia S.; Baldani, José I. (Frontiers in Plant Science, 2025)
Plant growth-promoting bacteria (PGPB) possessing 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity have the potential to enhance plant growth and development, particularly under adverse environmental conditions. This study aimed to identify bacterial strains with ACC deaminase activity able of mitigating the effects of water deficit stress and promoting the growth of Brachiaria genotypes. Bacterial strains isolated from Brachiaria genotypes were screened in vitro for ACC deaminase activity, and the presence of the acdS gene was confirmed via polymerase chain reaction (PCR) analysis. The bacterial isolates were screened for in vitro tolerance to water deficit stress, using 10% polyethylene glycol 8000 (PEG 8000) in association with B. ruziziensis and the effects of bacterial inoculation were assessed based on plant height and fresh biomass accumulation. Additionally, the association between endophytic bacterial strains and Brachiaria genotypes was evaluated using confocal laser microscope. The results showed that among the 213 strains tested, 32 demonstrate the ability to degrade ACC into α-ketobutyrate. ACC deaminase activity was detected in 17 strains, with values ranging from 1.98 to 102.52 μmol α-ketobutyrate mg-1 protein h-1. The presence of the acdS gene was confirmed in nine strains. The strains NRB142 (Paraburkholderia silvatlantica), NRB223 (Azospirillum melinis), and BR11790 (Herbaspirillum frisingense GSF30T) exhibited the most significant promotion of plant development in B. ruziziensis under water deficit stress mediated by 10% PEG 8000. Confocal microscopy analysis revealed the rhizospheric and inner root colonization of B. ruziziensis and B. brizantha cv. Paiaguás by the NRB142 mCherry-labeled strain. This study showed no predominance of a specific group of bacterial strains in terms of ACC deaminase activity. However, a subset of strains demonstrated the ability to colonize Brachiaria plants and mitigate the negative effects of water deficit stress. This study highlights the potential of ACC deaminase-producing bacteria in alleviating water deficit stress in Brachiaria plants supporting their use as a promising strategy for improving plant resilience under drought conditions.